Nursing as a pathway to women's empowerment and intergenerational mobility. Issue 21 (26th July 2018) - Brownie, Sharon; Wahedna, Abdul Haq; Crisp, Nigel
Abstract : Aim and objective: To assess the impact of nursing education on the intergenerational mobility of graduates of nursing upskilling programmes. Background: Challenges for low‐ and middle‐income countries include poverty and limited access to health, education and social services compounded by workforce shortages, inequality and female disempowerment. Little is known about the impact of nursing education on women's empowerment and intergenerational mobility in such settings. Design: A cross‐sectional study using data collected through an online alumni survey. Methods: Data were collected March to May 2016 using an online questionnaire, as part of a larger nursing programme alumni survey. Intergenerational mobility was assessed by comparing the respondents' educational qualification with their fathers' and mothers' education levels. Descriptive statistics were analysed using frequencies and percentages. Associations between parental and respondents' education levels were assessed using chi‐square tests. Results: Out of 446 female respondents who completed the survey, 379 and 366 indicated their fathers' and mothers' education level, respectively. A third of the respondents' mothers had no formal schooling; lower levels of parental education are significantly associated with increase in respondents age ( p  < 0.001) and associated shift from Uganda to Kenya and Tanzania ( p  < 0.001). Respondents had a marked upward intergenerational education mobility with 76% (278/366) and 59% (223/379) of them achieving a qualification two levels above their mothers and fathers, respectively. Tanzanian respondents had significantly higher rates of upward mobility than Kenyan and Ugandan respondents. Conclusions: Nursing education positively impacted gender, economic factors and health outcomes. Further research is needed to confirm the "triple impact" of nursing education on improving health, gender equality and economic growth in low‐ and middle‐income countries. Relevance to clinical practice: Nurses are frontline providers of healthcare services. Provision of high‐quality nursing upgrade programmes enhances nursing leadership ability, with aligned improvements in health outcomes while supporting gender empowerment and intergenerational mobility.